1972
DOI: 10.1017/s0022172400022610
|View full text |Cite
|
Sign up to set email alerts
|

The role of serum haemagglutination-inhibiting antibody in protection against challenge infection with influenza A2 and B viruses

Abstract: SUMMAlRYThe intranasal inoculation of volunteers with living partially attenuated strains of influenza A and B viruses offers a new opportunity to determine the protective effect of serum haemagglutin-inhibiting antibody against a strictly homologous virus, under conditions where the time and dosage of the infective challenge can be controlled, the scoring of proven infections can be more precise and higher rates of infection can be achieved than in most natural epidemics.In 1032 adult volunteers, whose serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
655
3
15

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 828 publications
(719 citation statements)
references
References 19 publications
24
655
3
15
Order By: Relevance
“…The cutoff value selected for a positive result was 1:40. HI antibody titers of ≥1:40 had been shown to correlate with reduction of 50% of the risk of contracting an influenza infection or disease9, 10, 11 and is frequently used as proxy for immunity. Thus, the term seroprevalence in this study refers to prevalence of antibody at titers of ≥1:40.…”
Section: Methodsmentioning
confidence: 99%
“…The cutoff value selected for a positive result was 1:40. HI antibody titers of ≥1:40 had been shown to correlate with reduction of 50% of the risk of contracting an influenza infection or disease9, 10, 11 and is frequently used as proxy for immunity. Thus, the term seroprevalence in this study refers to prevalence of antibody at titers of ≥1:40.…”
Section: Methodsmentioning
confidence: 99%
“…During inter-pandemic periods, influenza transmission occurs every year and antigenic drift contributes to epidemics of influenza A that occur every few years and are associated with excess mortality related to influenza-associated pneumonia in the very young and the elderly [1]. Existing influenza vaccines provide substantial protection when administered prior to exposure, and protective immunity is generally considered to be primarily dependent on neutralizing antibodies directed against HA [2,3], although there is evidence that antibodies against NA can also confer protection [4,5]. The only vaccines available for widespread use are inactivated vaccines prepared from influenza viruses grown in embryonated eggs, but their supply is limited, in large part by a paucity of specific pathogen-free eggs, and the need for new approaches to influenza vaccines is well recognized [6].…”
Section: Introductionmentioning
confidence: 99%
“…These cut‐offs stem from limited data from challenge studies conducted decades ago, demonstrating a relationship between HI titres and infection rates. These studies found that a pre‐challenge serum HI titre of 18–365 measured by HI assays or 42–446 measured by SRH assay correlated with 50% protection against infection. The serological response would be assessed by applying a set of criteria commonly referred to as the CHMP criteria (Table 1).…”
Section: Serological Correlates Of Protection: Moving Away From the Ementioning
confidence: 95%
“…However, influenza vaccines are intended not only to protect healthy adults but also to protect vulnerable children, older adults and adults with underlying comorbidities against consequences of natural infections with virulent influenza strains. Whether the correlates established in these challenge studies5 can be transferred to these situations has not been established. For example, one study identified that in children, an HI titre >1:110 would predict 50% of clinical protection and a titre of 1:330 would predict 80% of protection 11.…”
Section: Serological Correlates Of Protection: Moving Away From the Ementioning
confidence: 99%